2010
DOI: 10.1016/j.schres.2010.08.012
|View full text |Cite
|
Sign up to set email alerts
|

The case for including Attenuated Psychotic Symptoms Syndrome in DSM-5 as a psychosis risk syndrome

Abstract: The American Psychiatric Association Task Force on DSM-5 has recently proposed consideration of Attenuated Psychotic Symptoms Syndrome as a new diagnosis, based on nearly 15 years of prospective research in centers across the globe. The condition is also known as "psychosis risk syndrome," "at-risk mental state," "ultra-high risk," and "putative prodrome." We review evidence favoring its inclusion as a new diagnosis in DSM-5 and report new preliminary findings on DSM-IV diagnoses in current clinical use for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
84
0
6

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 109 publications
(91 citation statements)
references
References 84 publications
1
84
0
6
Order By: Relevance
“…For example, the subgroup comparisons showed that facilitative destigmatizing features of services were reported more frequently among at-risk than FEP groups. Rather than indicating experiential differences, this could reflect an increased interest in exploring positive aspects of detecting and treating high-risk states of psychotic illnesses, given the debate of whether risks of stigmatization outweigh the benefits of at-risk labels/services Woods et al 2010;Yang et al 2010), and a lack of research exploring this among FEP groups. Further, seemingly no studies have examined stigma and pathways to care among significant others of people in at-risk groups.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the subgroup comparisons showed that facilitative destigmatizing features of services were reported more frequently among at-risk than FEP groups. Rather than indicating experiential differences, this could reflect an increased interest in exploring positive aspects of detecting and treating high-risk states of psychotic illnesses, given the debate of whether risks of stigmatization outweigh the benefits of at-risk labels/services Woods et al 2010;Yang et al 2010), and a lack of research exploring this among FEP groups. Further, seemingly no studies have examined stigma and pathways to care among significant others of people in at-risk groups.…”
Section: Discussionmentioning
confidence: 99%
“…In the discussion about inclusion of an Attenuated Psychosis Syndrome based on APS in the fifth edition of the American Psychiatric Association's Diagnostic and Statistical Manual of Mental Disorders [12,13], it was, therefore, cautioned that APS might, in fact, be a common feature in adolescents and young adults from the general population and of no psychopathological significance by themselves [14,15]. …”
Section: Introductionmentioning
confidence: 99%
“…In addition to the debate held on the internet, many articles were published reflecting about the risks and benefits that the new diagnostic category could bring to the attention in mental health aimed at adolescents and young adults (Corcoran, First, & Cornblatt, 2010;McGorry, 2010;Yung, Nelson, Thompson & Wood, 2010;Woods et al, 2010). Among the risks discussed, there is a special highlight to false positives and the lack of safe information about the best options of treatment or intervention to be offered to this population.…”
Section: From a Clinical Strategy To The Proposal Of A Diagnostic Catmentioning
confidence: 99%